SEDIMENTARY COVER OF KARKINITSKA DEPRESSION: SYNTHETIC SEISMIC MODELLING - Kuzmenko , T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Upper and Lower Cretaceous sediments within Karkinitska depression are considered to be prospective for hydrocarbons. However, these stratigraphic thicknesses remain insufficiently explored, for only a few wells have been disclosed within the study area. This paper considers some aspects of building geological and geophysical models of hydrocarbon deposits and provides a perspective on their use in the modern exploration process. The aim of this study is to determine the ways of building the model for oil and gas-bearing deposits within Karkinitska depression in the Black Sea, in the case of the Gordievich structure. The singularity of the Gordievich structure is in the fact that there have been drilled no wells to evaluate the potential production of the deposits. The exploration for the Cretaceous sediments in the cut aided by synthetic seismic modeling allows for determining their properties that affect the seismic wave field. Synthetic seismic modeling helps to prepare seismic models of the Gordievich structure, which bears different reservoir properties (porosity, fluid saturation). The paper covers the findings in seismic surveys over the previous years. There have been analyzed seismic and geological environment based on synthetic modeling of seismic data – namely, on comparing a real wave field resulting from seismic acquisition with a set of synthetic wave fields (in the form of effective synthetic models) derived from seismic modeling. Comparing simulation data with real seismic data reveals that a synthetic model qualitatively reflects the parameters necessary for the wave field and the effects of dependencies between the cut heterogeneous porosity and fluid saturation. A dynamic similarity of the reflecting horizons is most concurrent for the Lower and Upper Cretaceous layers.
Keywords: seismic modeling; seismogeological cut; synthetic wave field